Application Of Fuzzy Algorithm In Decision Making On Honorary Signs - Farhaan Fadhlurrahman; Asnawati Asnawati; Devi Sartika (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Decision support system is an information generating system aimed at a particular problem that must be solved by the manager and assists the manager in decision making. Making a decision with many criteria requires a special handling method, especially if the criteria for making a model before the decision is taken. The SMART method is more often used because of its simplicity in responding to the needs of decision makers and analyzing responses. So the formulation of the problem in this study is how to implement the smart method of making honorary decisions. With the aim as comparative data in making decisions on honorary signs for members of the Indonesian National Police, Bengkulu Region. It is hoped that this application will always be up to date so that this application follows the development of Android-based technology with the flutter framework by utilizing the smart algorithm.